Corrosion protection of steel members using an Al-Zn base sacrificial anode and fiber sheet in an atmospheric environment. (10th November 2019) - Kainuma, Shigenobu; Yang, Muye; Ishihara, Shuji; Kaneko, Akira; Yamauchi, Takao
Highlights: A cathodic protection technique was developed for steel members in the atmospheric environment. Electrochemical studies on anodic alloy plates and galvanic coupling corrosion were performed. Exposure corrosion tests were carried out to evaluate the effectiveness and durability of system. Time-dependent anti-corrosion performance was assessed considering environmental variables. Abstract: A new cathodic protection technique for steel members in the atmospheric environment was developed in this study, Al-based alloy plate is a sacrificial anode, and fiber sheet was considered as electrolyte carrier. The reliabilities of components were clarified by comparing the material properties and electrochemical characteristics of alloy plates with different chemical composition. Besides, the galvanic current density and effective protection area of the corrosion protection system were discussed for solutions of various concentrations. Moreover, three types of corrosion tests were carried out to evaluate the effectiveness and durability of this system: the constant exposure test, accelerated exposure test, and atmospheric exposure test. The time-dependent anti-corrosion performance was discussed according to the characteristics of the corroded surface, and evaluated by discussing the effect of environmental variables and the exposed holes of the anode plates. The test results show that the sensitivity of the specimens to the changes in the environment is low, and that the cathodic protection current flows continuously, irrespective of whether it rained or not. In addition, the anode consumption of an Al-20Zn (mass%) alloy plate is the least, with good current efficiency, and an improvement in the anti-corrosion effect by adding elemental In to the anode plate cannot be expected. For all the test specimens, the current efficiency of the sacrificial anodes could on average reach about 70–80% in this system.